Upaya Peningkatan Kualitas Sumber Daya Manusia di SMAN 1 Palibelio Kabupaten Bima - Faridah, Faridah; Suncaka; Sri Fatmawati (UNISAN JURNAL, 2025)
This study aims to describe various efforts undertaken by SMAN 1 Palibelo, Bima Regency, to improve the quality of human resources (HR) during the 2024/2025 academic year. Enhancing HR quality within schools is a key factor in achieving high-quality and competitive education in the era of globalization. This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal, teachers, education staff, and students. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings revealed that efforts to improve HR quality at SMAN 1 Palibelo were carried out through several key strategies, namely: (1) developing teacher competencies through training, workshops, and teacher working group (KKG/MGMP) activities to strengthen professional skills; (2) enhancing the discipline and work ethic of education staff through regular supervision and evaluation systems; (3) fostering students’ character through extracurricular programs, literacy activities, and habituation of religious and national values within the school environment; and (4) optimizing the use of information technology in both teaching and school management processes. The main supporting factors for the success of HR development programs at SMAN 1 Palibelo include visionary school leadership, support from the school committee, and a collaborative spirit among school members. However, the study also identified several challenges, such as limited training facilities, time constraints for self-development, and varying levels of teachers’ digital literacy. Overall, the findings indicate that the efforts to improve HR quality at SMAN 1 Palibelo have been implemented systematically and sustainably, although further strengthening is needed in innovation and program evaluation aspects.